Challenges And Strategies For The Improvement Of Water Management In Bhopal - Dehalwar, Kavita; Singh, Jagdish (European Scientific Journal, ESJ, 2016)
Bhopal is gradually being transformed into a metropolitan city due to its high developmental trajectory and its vast population size. Although she has earned the reputation of ‘City of Lake’ owing to her large number of ponds and lakes, she is insufficient in catering for the ever growing needs of her entire populace. Many natural and anthropogenic activities and occurrences such as unplanned infrastructural development, short- lived rainfall coupled with inefficient management of solid waste as well as inadequacy in skilled-manpower, are all responsible for this. In the current scenario, strategies such as the employing of technical-know-how and the engaging of Community Based Organizations are being utilized for the managing of this problem. Other invaluable efforts for the building of the social capital would be needed for the enlargement of the government’s reach in order to install the effective sustainable water management.